Optimizing the potential of Karangtengah village through educational parks and Cananga herbal cafe - Amelia Sholu Pratiwi; Aji Tetuko; Fatimah Nur Azizah; Ni Putu Dea Anantarini (Universitas Muhammadiyah Magelang, 2023)
Karangtengah Village, one of the villages in Bantul Regency, has a rich potential for biodiversity, particularly for family medicinal plants. However, there are still a lot of undeveloped lands that could be better utilized. This program aims to increase community independence in terms of supporting families by encouraging land use or vacant yard optimization. The Karangtengah Village Farmer's Group and PKK women were the targets of this program. The team will transform a plot of land in Karangtengah Village into an educational park and herbal cafe called